Elaboração de um guia para avaliação de relatórios de segurança/eficácia apresentados à ANVISA em petições de registro, renovação de registro e pós-registro de medicamentos específicos, fitoterápicos e dinamizados - Pietro, David Edgard (2020)
The concern to identify which practices are responsible for disease prevention and treatment is ancient. From the development of the need to understand and control factors that impact the population's health, emerge the first modern concepts of health surveillance in the 18th century. The early regulations on medicines sought to ensure quality and prevent adulteration of pharmaceutical products and the raw materials used in their manufacture. Concern about safety and efficacy aspects would only take place in the regulations after tragic episodes involving medicines in the 20th century. Thus, was developed the concept of drug marketing authorization, based on the need of evidences of quality, safety and efficacy before they are made available to the population. In this context, the evidence of safety and efficacy of a drug is based on the principles of Evidence-Based Medicine (EBM), an approach in which health decision-making relies on the most reliable evidence available. In the EBM approach Randomized Controlled Trials (RCT) are considered the source of most reliable evidence, however, a poorly designed or improperly conducted RCT conceals biases that may affect the study's conclusions. Therefore, RCT assessment tools were created to identify how much confidence we can have in the results and conclusions of a study. The objective of this paper was to develop a Guide for the evaluation of safety and efficacy reports submitted to Anvisa in petitions for marketing authorization, renewal of marketing authorization and post-market changes of specific drugs, herbal drugs and homeopathics. To achieve this purpose, the regulatory requirements to prove the safety and efficacy of these drug categories were identified, RCT assessment tools available in the scientific literature were reviewed and guidelines on safety and efficacy of medicines published by Anvisa and foreign health authorities were consulted. The Guide was built on the Limesurvey electronic platform. The implementation of the Guide proposed in this dissertation at Anvisa's work routine will result in more effective and standardized dossier analysis and also in a reduction on marketing authorisation refusal and information request related to medicines safety and eficacy.